Combined Axillary Block with Spinal Block Anaesthesia - Arsil Radiansyah; John Frans Sitepu; Luwih Bisono (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2022)
Background: Patients undergoing upper limb trauma surgery have reported various benefits of regional anesthesia over general anesthesia, including better perioperative analgesia, less opiate use, less postoperative nausea and vomiting (PONV), and a shorter post-anesthesia care period. …………………………….. Case Illustration: We reported an evaluation of 72 years old, 165 cm height and 60 kg weight male patient who was planned for open reduction and internal fixation surgery for neglected left radius ulna close fracture and left neglected tibia fibula close fracture that he was beneath follow-up for hypertension (HT), and was using antihypertensive drugs. Preoperative risk of the patient was assessed as with American Society of Anesthesiologists (ASA) with score 3.General anesthesia would be unsafe due to geriatric issue, cardiovascular problem and delayed surgery term, we chosed to utilize combine axillary block with spinal block. we utilized USG guided infusion procedure in arrange to diminish local anesthetic dosage, and minimize error. During surgical procedure there is no hypotension, bradycardia or decreased oxygen saturation. Surgical anesthesia occurred in left hand within 20 minutes after drug delivery and 10 minutes in lower extremity. Surgery complications was not reported particularly related to vascular punction or adjacent anesthetic and nerve block applications. No complaint was detailed from the patient who was watched for 12 hours after the surgery.Conclusion: Peripheral nerve block and neuraxial block, when utilized appropriately in combination, appear be able to supplant common anesthesia within the larger part of case.